Transferring differentiation and integration through picking up students’ speech by hip-hop and its appreciation - Janiec , Jerzy (Kultura-Społeczeństwo-Edukacja, 2020)
Janiec Jerzy, Transferring differentiation and integration through picking up students’ speech by hip-hop and its appreciation. Culture – Society – Education no 2(16) 2019, Poznań 2019, pp. 23–44, Adam Mickiewicz University Press. ISSN 2300-0422. DOI 10.14746/kse.2019.16.2. The main aim of this paper is to demonstrate the Hip-hop based Education (HHBE) and Hip-hop Pedagogy (HHPED) as two accommodating strategies that may be utilized fourishingly to differentiate a teaching-learning process further to integrate learners in any education-like environment, as the example the IB World School No. 006654 International School of Bydgoszcz (ISOB) has been chosen. This is the first study presenting international community in a truly homogeneous society (ca. 98% of Polish inhabitants in their country). The author enlists affirmative methodologies beginning with a hypothesis that the Hip-hop culture is gaining popularity among adolescents in greater numbers. As a result of observations, interviews and survey he is acquainted with students’ wants and needs. There is a necessity to put them in a bigger picture by analyzing the phenomenon from a historical, sociological, political, economical and intercultural viewpoint on a local (Bydgoszcz’s) and global scale. And finally, the author is describing a use of the aforesaid strategies through transfer skills that are taught in the IB History and Social Studies classes.